THE RELATIONSHIP BETWEEN EPILITHIC DIATOM COMMUNITIES AND WATER QUALITY VARIATIONS ACROSS TOHMA STREAM (MALATYA-TURKEY) - Yildirim, Vesile; Baran, Nilgun (Parlar Scientific Publications (P S P), 2019)
Epilithic diatom community of Tohma Stream, as well as physicochemical properties of the stream were studied through samples collected from the specified 4 stations in monthly periods for one year. 70 species from 21 genera were identified in the study. In epilithon in the stations, Navicula spp. (16 taxa) was the most remarkable genus in terms of both number of species and the number of individuals from species and this was followed by Cymbella (13 taxa) and Nitzschia (9 taxa). The water quality in the Tohma stream varied at different stations based on levels of pollution. The epilithic diatom communities responded to changes in the aquatic environment. Dominant species had variation among the stations. Dominant species of the station 1 were Cocconeis placentula, Diatoma vulgaris, Cymbella affinis and Gomphonema olivaceum. Navicula cryptocephala, C. minuta, Ulnaria ulna, Nitzschia amphibia, and N thermalis were dominant diatoms of the stations 2 and 3. Dominant diatoms of the station 4 were Achnanthidium minutissimum, N palea, Gomphonema parvulum, and Surirella angustata, diversity of diatoms also varied in all stations in parallel to water quality. Also, station 4 in Beyler Brook in which wastes of 1st and 2nd Organized industry zones are discharged joins to Tohma stream. We concluded that Tohma stream has a water quality gradient and this led to apparent variances in species composition of diatom across the stream. The results have confirmed that epilithic diatoms are crucial biological indicators to evaluate ecological quality of Tohma stream.
Keywords: Tohma Stream; Epilithic diatoms; Water quality; Pollution